TEMPORAL CHARACTERISTIC PSYCHOACOUSTIC ANALYSIS OF GENDING BAPANG MALANGAN PADEPOKAN MANGUN DHARMA VERSION - Oeky Prasetio Widya Susanto; Akhmad Farid; Nurida Finahari (Universitas Muhammadiyah Semarang, 2022)
In the Malangan mask dance drama, the dance is accompanied by the strains of gending. Padepokan Mangun Darma Tumpang's version of Gending Bapang is the longest, according to the duration of the dance and the highest diversity of movements. This makes the Bapang dance and music version of the Mangun Darma hermitage a complete object of study, which can be used as a reference for other versions of Bapang research. This article aims to examine the temporal aspect of Bapang Malangan's music from the point of view of psychoacoustic studies. The temporal aspect is related to time-based vibration (sound) variables that are real time. Gending analysis is done using a sound processing application called Audacity. The research data will be converted into a temporal graph t (time) - A (amplitude). The temporal chart pattern will be analyzed for the strength and weakness of the voice, the dynamics of the sound, and the musical character. The results of the graphic analysis will be used as the basis for making a discussion about psychoacoustic gending. The results showed that the Bapang Malangan music version of Padepokan Mangun Dharma Tumpang Malang had a score of 4 which was the category of music therapy. Temporal characters represented by sound intensity have an average of 28.7 dB for the left sound and 30.1 dB for the right voice. This makes this gending does not include harmful noise.